2002
DOI: 10.3354/meps240183
|View full text |Cite
|
Sign up to set email alerts
|

Midnight sinking behaviour in Calanus finmarchicus: a response to satiation or krill predation?

Abstract: The vertical migration of Calanus finmarchicus and krill (Meganyctiphanes norvegica and Thysanoessa raschii ) was monitored during the summer of 1999 in the Clyde Sea using a combination of acoustic and net sampling methods. A moored 300 kHz acoustic Doppler current profiler (ADCP) identified a sound scattering layer (SSL) that started to ascend to the surface during the last moments of daylight. Net samples showed that the SSL was mostly composed of krill. C. finmarchicus rose to the surface in the late after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 37 publications
2
45
0
1
Order By: Relevance
“…Two basic types of DVM patterns are identified: in Type I migrations, organisms ascend to the surface before the onset of night (dusk) and down to daytime depths with day break (dawn), although nocturnal vertical relocations between dusk and dawn ('midnight sinking') can occur (Giske et al 1990, Tarling et al 2002, BenoitBird et al 2009). In the reverse Type II migrations, organisms ascend in daytime and descend at night (Neilson & Perry 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Two basic types of DVM patterns are identified: in Type I migrations, organisms ascend to the surface before the onset of night (dusk) and down to daytime depths with day break (dawn), although nocturnal vertical relocations between dusk and dawn ('midnight sinking') can occur (Giske et al 1990, Tarling et al 2002, BenoitBird et al 2009). In the reverse Type II migrations, organisms ascend in daytime and descend at night (Neilson & Perry 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Simard et al 1985). Midnight sinking has also been attributed to predator avoidance behavior (Tarling et al 2002(Tarling et al , 2003; however, those observations have also been interpreted in different ways (Pearre 2003). Our study did not measure predation; our intent was to determine the seasonal variability in the foray foraging behavior.…”
Section: Discussionmentioning
confidence: 99%
“…4) were (1) Tarling et al 2000Tarling et al , 2002 tiple opening and closing net samples (MOCNESS) giving depth-stratified abundance estimates of adult Meganyctiphanes norvegica (28 June-1 July 1999: Tarling et al 2000Tarling et al , 2002. Tarling et al (2002) showed that the majority of backscatter was caused by krill. All DVM patterns were expressed as mean and standard deviation of depth occupied per hour by weighting each depth by the estimated backscatter or proportional abundance at that depth (Fig.…”
Section: Comparison Of Model Predictions With Observed Patterns Of DVmentioning
confidence: 99%